The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12882-018-0908-3
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of human leukocyte antigen mismatching on graft survival and mortality in renal transplantation? A meta-analysis of 23 cohort studies involving 486,608 recipients

Abstract: AbstractsBackgroundThe magnitude effects of human leukocyte antigen (HLA) mismatching on post-transplant outcomes of kidney transplantation remain controversial. We aim to quantitatively assess the associations of HLA mismatching with graft survival and mortality in adult kidney transplantation.MethodsWe searched PubMed, EMBASE and the Cochrane Library from their inception to December, 2016. Priori clinical outcomes were overall graft failure, death-censored graft failure and all-cause mortality.ResultsA total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 44 publications
(51 reference statements)
4
32
1
4
Order By: Relevance
“…This led to a significant reduction in acute rejection episodes and improved one‐year renal allograft survival. Nevertheless, recent analyses confirmed that HLA serotype level mismatch remains associated with both acute rejection episodes and graft survival in large cohorts .…”
Section: A Brief Summary Of the Current Understanding Of Alloimmunitymentioning
confidence: 99%
“…This led to a significant reduction in acute rejection episodes and improved one‐year renal allograft survival. Nevertheless, recent analyses confirmed that HLA serotype level mismatch remains associated with both acute rejection episodes and graft survival in large cohorts .…”
Section: A Brief Summary Of the Current Understanding Of Alloimmunitymentioning
confidence: 99%
“…HLA mismatch might be one reason for rejection [14,40]. HLA A and especially HLA DR mismatches correlated with a higher incidence of rejection and graft loss [14,16,35,41].…”
Section: Plos Onementioning
confidence: 99%
“…HLA mismatch might be one reason for rejection [14,40]. HLA A and especially HLA DR mismatches correlated with a higher incidence of rejection and graft loss [14,16,35,41]. A low HLA mismatch should therefore be aimed for reduced numbers of rejection and their influence on graft survival [16,41].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The increased longevity of grafts transplanted in accordance with lower HLA mismatched loci is well-known [41] and has been confirmed in a meta-analysis of over 480 000 transplanted patients. [42] HLA typing and consequent matching of HLA donor-to-recipient phenotype forms an integral part of the bone marrow graft allocation protocol internationally as well as in the SA transplantation fraternity. Among other criteria for patients awaiting transplantation, novel strategies are being employed to establish improved HLA matching between unrelated living donors and recipients.…”
Section: Hla Applicationsmentioning
confidence: 99%